Improve key performance indicators with AI - Schrage, Michael; Kiron, David; Candelon, François; Khodabandeh, Shervin; Chu, Michael (MIT Sloan Management Review, 2023)
In this second article in a series of four, the researchers behind the 2023 MIT Sloan Management Review-BCG Artificial Intelligence and Business Strategy Big Ideas research project offer a framework — improve-create-establish, or ICE — for enhancing strategic measurement with artificial intelligence. Examples from companies such as Wayfair and DBS Bank help illustrate the potential benefits of using AI to improve KPIs.